Nursing students’ experiences of case-based learning in medical-surgical nursing courses: A phenomenological qualitative - Devia Putri Lenggogeni; Hema Malini; Esthika Ariany Maisa; Bunga Permata Wenny; Mahathir Mahathir (School of Health Sciences Al-Ma'arif, 2026)
Background: Case-Based Learning (CBL) method is interactive and utilizes actual or realistic scenarios to promote authentic learning. It is an interactive, student-centred exploration that begins with illustrating real-life situations. CBL combines a constructivist and experiential approach, developing professional skills such as problem-solving, clinical reasoning, and knowledge of theory. Objective: This study aimed to explore students' experiences in using CBL learning method in medical-surgical nursing courses at Faculty of Nursing, Universitas Andalas. Methods: This study used a descriptive phenomenological qualitative design. Twenty-three fifth-semester nursing students enrolled in medical-surgical nursing courses using CBL were selected through purposive sampling. Data were collected in July 2022 through three focus group discussions lasting 60–90 minutes, guided by semi-structured questions on students’ perceptions, benefits, challenges, and suggestions for CBL implementation. Audio recordings were transcribed verbatim and analyzed using the Stevick-Colaizzi-Keen phenomenological method. Trustworthiness was ensured through credibility, transferability, dependability, and confirmability. Results: Based on the results of the thematic analysis, several themes were found, including (1) CBL learning method develops analytical thinking students (2) Using cases in CBL learning method improves the quality of learning (3) Inappropriate standard of implementation CBL learning methods. Conclusion: This study showed some benefits of using CBL learning method. Based on the results, it is necessary to optimize the implementation of CBL in medical-surgical nursing courses and develop it in other courses in Faculty of Nursing, Universitas Andalas.